Control of Power and Voltage of Solar Grid Connected - Boucetta Abd Allah; Labed Djamel (Bulletin of Electrical Engineering and Informatics, 2016)
Renewable energy is high on international agendas. Currently, grid-connected photovoltaic systems are a popular technology to convert solar energy into electricity. Control of power injected into the grid, maximum power point, high efficiency, and low total harmonic distortion of the currents injected into the grid are the requirements for inverter connection into the grid. Consequently, the performance of the inverters connected to the grid depends largely on the control strategy applied. In this paper the simulation and design of grid connected three phase photovoltaic system using Matlab/Simulink has examined. The proposed system consists photovoltaic panels, boost and inverter the PV system convert the sun irradiation into direct current, thereafter we have used a boost to track the maximum power point of the PV system, three-phase inverter and LC output filter. A VOC control strategy based on the phase shifting of the inverter output voltage with respect to the grid voltage. The proposed control strategy requires few hardware and computational resources. As a result, the inverter implementation is simple, and it becomes an attractive solution for low power grid connected applications.